Possible early detection of coronary artery calcium progression in type 1 diabetes: A case-control study of normoalbuminuric type 1 diabetes patients and matched controls. (July 2018) - Hjortkjær, Henrik Ø.; Jensen, Tonny; Hilsted, Jannik; Corinth, Helle; Mogensen, Ulrik M.; Køber, Lars; Fuchs, Andreas; Nordestgaard, Børge G.; Kofoed, Klaus F.
Highlights: Type 1 diabetes patients have partly unexplained increased cardiovascular (CV) risk. Progression of coronary artery calcium (CAC) is an important CV risk marker. Early detection of CAC progression may be clinically relevant. First study examining short-term progression in type 1 diabetes and matched controls. We report increased progression of CAC in type 1 diabetes after just two years. Abstract: Aims: Coronary artery calcium (CAC) is associated with cardiovascular (CV) disease and progression of CAC is an independent predictor of mortality. Type 1 diabetes is associated with increased CV risk, especially in persons with cardiovascular autonomic neuropathy (CAN). This study aimed to examine whether short-term progression of CAC is increased in persons with type 1 diabetes compared to matched controls and if CAN increases risk of CAC progression. Methods: Fifty-three normoalbuminuric persons with long-term type 1 diabetes (20 with CAN) were matched in a 1:2 ratio with 106 controls without diabetes according to age, sex and baseline CAC. All were examined twice with cardiac computed tomography scans. Progression of CAC was defined as a value ≥2.5 between the square root-transformed values of follow-up and baseline CAC volume scores. Results: The participants were examined median (interquartile range) of 25 (23–27) months (type 1 diabetes) and 29 (25–33) months (controls) apart. In multivariable logistic regression, participants with type 1 diabetes had an odds ratio of 3.3 (95% CI 1.3–8.2, p = 0.01) for CAC progression. CAN did not increase progression of CAC (p = 0.64). Conclusions: Progression of CAC was increased in well-treated, normoalbuminuric persons with type 1 diabetes compared to matched controls without diabetes, suggesting that type 1 diabetes is a risk factor for short-term progression. This finding could explain some of the increased morbidity and mortality observed in persons with type 1 diabetes, but it does not specifically explain the increased CV risk in persons with CAN.